EFEKTIFITAS LAYANAN PEMBUATAN SURAT IZIN MENGEMUDI (SIM) DI SATLANTAS POLRESTABES SEMARANG - Kiswo Pramono (Fakultas Hukum Universitas Stikubank, 2021)
The effectiveness of making a SIM is deemed to have to refer to Law no. 14 of 2008 concerning Public Information Disclosure and Standard Operating Procedures for Public Information Disclosure of the Police. It was explained that in the reform era every citizen has the right to seek, obtain, use and disseminate accurate information easily and quickly. The National Police of the Republic of Indonesia to provide information/public services to ensure transparent and accountable public information services from planning, implementation to publication of information through mass media. The effectiveness of the Service for Making a Driving License (SIM) in the perspective of service users at the Semarang Polrestabes Satlantas and about the effectiveness of making a SIM at the Semarang Polrestabes Satpas, we can know that service is a complete approach that results in quality service for the community/customers. Consists of Transparency, Accountability, Conditional, Participatory, Equality of rights and Balance of rights and obligations. Keywords: service, effectiveness, SIM